2016
DOI: 10.1111/jpc.13243
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency and xerophthalmia in children of a developed country

Abstract: Vitamin A deficiency and xerophthalmia do exist in children of developed country. The potential for xerophthalmia should be considered, and there should be a consideration of an ophthalmology review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 22 publications
0
31
0
4
Order By: Relevance
“…Surprisingly, approximately 5% of our study population had true vitamin A deficiency and 38% had subclinical vitamin A deficiency regardless of group assignment. Since most studies on vitamin A deficiency are carried out in developing countries, it is difficult to draw conclusions relevant to developed countries, such as Israel . The definitions of normal concentrations of vitamin A and specifically of vitamin A deficiency are based on the levels of vitamin A causing the clinical spectrum of ocular manifestations of vitamin A deficiency for example in xerophthalmia as reported by the World Health Organization report .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, approximately 5% of our study population had true vitamin A deficiency and 38% had subclinical vitamin A deficiency regardless of group assignment. Since most studies on vitamin A deficiency are carried out in developing countries, it is difficult to draw conclusions relevant to developed countries, such as Israel . The definitions of normal concentrations of vitamin A and specifically of vitamin A deficiency are based on the levels of vitamin A causing the clinical spectrum of ocular manifestations of vitamin A deficiency for example in xerophthalmia as reported by the World Health Organization report .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to test for other nutritional deficiencies, such as zinc and B12 deficiencies, that may also contribute to similar ocular manifestations as they often coexist . Vitamin A deficiency can also impair iron metabolism and haematopoiesis, leading to anaemia . Studies have shown multi‐nutrient deficiencies in Australian and New Zealand children, with up to 25% with iron deficiency without anaemia and 10% with anaemia .…”
Section: Discussionmentioning
confidence: 99%
“…Other subgroups at risk in a developed country include families on restrictive diets such as vegetarianism, children with chronic disease such as cystic fibrosis that is known to impair vitamin A metabolism and children with autism or other mental health illness that is associated with picky eating behaviours . Picky eating behaviour is increasingly more common in Western society and is known to be associated with nutrient deficiency .…”
Section: Discussionmentioning
confidence: 99%
“…La deficiencia de vitamina A constituye un grave problema de salud pública en los países de bajos ingresos, su principal causa es el déficit crónico de vitamina A en la dieta, lo que lleva a bajos depósitos orgánicos de retinol y, cuando es persistente, afecta directamente varias funciones como el crecimiento tisular, el metabolismo y la resistencia a las infecciones (1). En casos graves, cuando el aporte de la dieta de cualquiera de las formas de vitamina A es muy bajo por un tiempo prolongado, conduce a la xeroftalmía, primera causa de ceguera infantil prevenible, a la disminución de la resistencia a las infecciones y a un mayor riesgo de mortalidad (2). Los niños pequeños y las mujeres gestantes son los grupos más vulnerables a dicha deficiencia (2,3).…”
Section: Introductionunclassified
“…En casos graves, cuando el aporte de la dieta de cualquiera de las formas de vitamina A es muy bajo por un tiempo prolongado, conduce a la xeroftalmía, primera causa de ceguera infantil prevenible, a la disminución de la resistencia a las infecciones y a un mayor riesgo de mortalidad (2). Los niños pequeños y las mujeres gestantes son los grupos más vulnerables a dicha deficiencia (2,3). La función primordial de la vitamina A se encuentra principalmente en el ojo, donde tiene dos tareas importantes: mantiene las estructuras oculares y participa en la conversión de la luz a impulsos nerviosos en la retina (4,5).…”
Section: Introductionunclassified